The Contribution of Islamic and Conventional Banks to Financial Stability in Indonesia - Faaza Fakhrunnas; Katiya Nahda; Mohammad Abdul Matin Chowdhury (Faculty of Economic and Business, 2023)
This study aims to examine an asymmetric relationship between Islamic and conventional bank contributions to financial stability in Indonesia. Adopting non-linear autoregressive distributed lag (NARDL), the study utilizes time-series data from 2004m1-2021m9, consisting of financial stability as a dependent variable, proxied by non-performing loans (NPLs) and ZSCORE. Islamic and conventional banks as independent variables were measured by total financing and total assets. Furthermore, we used interest rates and inflation as complementary variables. The findings reveal that Islamic and conventional banks affect financial stability in the short and long run. However, conventional banks contribute to financial stability more than Islamic banks. The asymmetric relationship explains that an increase/decrease in the independent variables to the same degree does not have the same impact on the dependent variable. This research implies that the financial authorities need to increase their awareness of the presence of asymmetric relationships when designing monetary policy to achieve and maintain financial stability. Finally, the study also fills the current research gap by measuring the contribution of Islamic and conventional banks to financial stability from an asymmetric relationship viewpoint.JEL Classification: E60, G20, G21How to Cite:Fakhrunnas, F., Nahda, K., Chowdhury, M.A.M. (2023). The Contribution of Islamic and Conventional Banks to Financial Stability in Indonesia. Etikonomi, 22(1), 213–232. https://doi.org/10.15408/etk.v22i2.26656.